Impact of COVID-19 on Elective Surgical Lists in Otorhinolaryngology: An Overview - Memoona Afzal, Tabassum Aziz, Nausheen Qureshi, Sundas Masood, Fatima Shahid, Asmara Hussain, Memoona Afzal, Tabassum Aziz, Nausheen Qureshi, Sundas Masood, Fatima Shahid, Asmara Hussain (Journal of Rawalpindi Medical College, 2021)
Objective: To study how the COVID-19 is affecting the treatment and management of other ailments. Try to find a strategy to resume elective OR lists. Introduction: We overviewed the effect of COVID-19 on the elective surgical lists of otorhinolaryngology in the ENT Department of Holy Family Hospital, Rawalpindi. Materials and Methods: The data from Jan 2020 to July 2020 was collected. It is a descriptive study analyzing the data, 3 months before and 3 months after the imposition of lockdown in the whole of Pakistan due to a surge in COVID-19 cases. The data was collected from the operation dating register of OPD and elective operative lists of ENT OT. Data were analyzed by Microsoft excel spreadsheet version 7. Results: There was an overall 92% decrease in the elective surgical procedures done in the ENT dept. of Holy family Hospital during the COVID-19 lockdown period. The procedures done in the COVID lockdown period were mostly emergency procedures and lifesaving procedures. Conclusion: COVID-19 has badly impacted the elective surgical procedures and in turn the health of the patients presenting to ENT OPD with various diseases which were treated surgically before COVID lockdown. Recommendations: To prevent this from happening again during the 2nd wave of COVID-19, we could opt for multiple precautionary measures to avoid the spread of infection and continue the provision of our surgical services to the patients.